2021
DOI: 10.1097/01.asw.0000725168.11099.92
|View full text |Cite
|
Sign up to set email alerts
|

Pilonidal Sinus Disease: An Analysis of the Factors Affecting Recurrence

Abstract: OBJECTIVE To assess the success of treatment methods at reducing recurrence, the most important problem in pilonidal sinus disease (PSD), along with factors affecting the occurrence of PSD and posttreatment recurrence. METHODS The researchers retrospectively analyzed files of patients treated for PSD between 2003 and 2018. Three study groups were created: G1, G2, and G3. G1 included all PSDs with recurrence, and a comparable number of cases without recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 11 publications
0
6
0
2
Order By: Relevance
“…recognised, suggesting that the cause of pilonidal sinus lies in hard hair, skin injury, hair suction by the skin and other factors. 14 However, factors such as local soft tissue injury, prolonged sitting, hair hardness, and local longterm irritation are all high-risk factors for the disease. There are already lots of studies focusing on SPS, and its ideal treatment is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…recognised, suggesting that the cause of pilonidal sinus lies in hard hair, skin injury, hair suction by the skin and other factors. 14 However, factors such as local soft tissue injury, prolonged sitting, hair hardness, and local longterm irritation are all high-risk factors for the disease. There are already lots of studies focusing on SPS, and its ideal treatment is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…As the hair detaches from the root, suction generated within the cuticularized fine channel sucks into the channel, which leads to sinus formation 12,13 . In recent years, the acquired theory has been mostly recognised, suggesting that the cause of pilonidal sinus lies in hard hair, skin injury, hair suction by the skin and other factors 14 . However, factors such as local soft tissue injury, prolonged sitting, hair hardness, and local long‐term irritation are all high‐risk factors for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro del importante arsenal de patologías perianales, las más frecuentes y por las que suele acudir a consulta los pacientes son las hemorroides, la fisura anal, la fístula anal, el sinus pilonidal y la hidradenitis perianal 6 . Entre la fisiopatología de un parte de estas afecciones, la obesidad juega un papel importante en algunas de ellas [7][8][9] . El objetivo de nuestro estudio es realizar una descripción y análisis sobre la patología anal benigna en pacientes obesos mórbidos candidatos a cirugía bariátrica.…”
Section: Anal Disease In Patients Who Are Candidates For Bariatric Su...unclassified
“…En el estudio presentado se describe la incidencia de la patología perianal benigna en la población obesa candidata a cirugía bariátrica. Los resultados de nuestro estudio muestran que se trata de enfermedades con alta prevalencia, y que tienen impacto en la calidad de vida de los pacientes, siendo muchas veces infradiagnosticadas [7][8][9] . La enfermedad hemorroidal es una patología frecuente.…”
Section: Discusionunclassified
“…The risk factors for SPS mainly include obesity, sedentary lifestyle, excessive body hair, family history, and poor hygiene habits 15 . In a recent study, oily and dark skin were also found to be risk factors for the development of an SPS 16 . In addition, in a retrospective study with a median follow-up time of 42 months, Li and colleagues used MRI to accurately measure the basic parameters (size, volume, position, surrounding tissue) of the SPS.…”
mentioning
confidence: 92%